PENGEMBANGAN MEDIA BIG BOOK DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK PADA PELAJARAN BAHASA INDONESIA KELAS III DI SDN 07 SITIUNG - Rhenita Suci Anggriani; Ana Novitasari; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop digital big book media to improve students' reading skills in class III Indonesian language lessons at Sdn 07 Sitiung because looking at the phenomenon in this school, the use of learning media is still conventional, teachers still focus on textbook teaching resources only, and Students' reading achievement is still low and the use of learning media can attract students' attention in the teaching and learning process. The type of research used by researchers is Research and Development or what is known as ADDIE development. This model consists of five stages, namely the analysis, design, development, implementation and evaluation stages. This development research has passed several tests, namely: (1) media validation by validators 82.5% in the "valid" category. Material validation by validators 90% in the "valid" category. Language validation by validators is 82.5% in the "valid" category. Validation of teaching modules by validators is 80% in the "valid" category. Based on validation trials, it can be concluded that the development of digital big book media can be used to improve participants' reading skills. educate.